Implementation of the moodle platform in the ninth grade social studies classroom, as a means to reinforce the acquisition of English as a foreign language - Pareja Montesinos, Clara Lucía (2012)
The need to learn continuously throughout life has become a permanent concern in society. Not many years ago, an individual who finished High School, was prepared for a lifetime. Formerly, a high school diploma was sufficient; later on, a university degree became a must. Today, people must spend their entire life learning, and the university degree is only the first step along the way; the individual must study constantly and the need to update his knowledge, becomes compulsory. Continuous professional and occupational training seems to be the mechanism used, in order to reshape the basic education acquired, either to fit the individual’s needs or those of the organization the person works for. Learning, from this perspective, is a lifetime process that starts with birth and extends all the way to death. It is both, a conscious and unconscious procedure. Taking into account how learning takes place, innumerable investigations have been carried out to determine the best approaches, methodologies, resources, and materials to ensure students’ success. Since unconscious learning occurs in a natural environment, professional researchers on the area have been trying to replicate such ambiance to make the learning process more effective and less demanding to students. As any teacher of many years of experience will attest, whenever students are really interested in something, they will put all their effort in learning about it. Under those circumstances they will use all their skills to look for information and they will get deeply immersed...